2021
DOI: 10.1016/j.joca.2020.10.003
|View full text |Cite
|
Sign up to set email alerts
|

Proof-of-concept for the detection of early osteoarthritis pathology by clinically applicable endomicroscopy and quantitative AI-supported optical biopsy

Abstract: Objective: Clinical trials for osteoarthritis (OA), the leading cause of global disability, are unable to pinpoint the early, potentially reversible disease with clinical technology. Hence, disease-modifying drug candidates cannot be tested early in the disease. To overcome this obstacle, we asked whether early OApathology detection is possible with current clinical technology. Methods: We determined the relationship between two sensitive early OA markers, atomic force microscopy (AFM)-measured human articular… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 51 publications
0
16
0
Order By: Relevance
“…OA has become a worldwide medical burden, and thus far, there have been no available preventive or therapeutic biological interventions. 29 This study aimed to discover a therapeutic drug for OA. Chondrocytes were treated with TNF-α to mimic the inflammatory environment, and engeletin was then administered.…”
Section: Discussionmentioning
confidence: 99%
“…OA has become a worldwide medical burden, and thus far, there have been no available preventive or therapeutic biological interventions. 29 This study aimed to discover a therapeutic drug for OA. Chondrocytes were treated with TNF-α to mimic the inflammatory environment, and engeletin was then administered.…”
Section: Discussionmentioning
confidence: 99%
“…Another approach is to focus on other diagnostic imaging techniques to diagnose the early and potentially reversible disease pathology, especially since methods, such as X-ray and MRI cannot yet statistically discriminate between healthy vs. early OA [239]. We recently showed that a clinically available confocal laser endomicroscope could be used to image a surrogate marker of otherwise clinically, but not yet detectable, early OA functional pathology prior to cell clustering [240]. Specifically, we showed that characteristics of the spatial organization of the superficial zone chondrocytes (SCSO) are indicative of early pathology [94,[107][108][109][110]136,241] and can be imaged clinically using a confocal laser endomicroscope.…”
Section: Summary Outlook and Early Disease Considerationsmentioning
confidence: 99%
“…Specifically, we showed that characteristics of the spatial organization of the superficial zone chondrocytes (SCSO) are indicative of early pathology [94,[107][108][109][110]136,241] and can be imaged clinically using a confocal laser endomicroscope. Combined with random forest modelling, this artificial intelligence (AI)-based non-destructive quantitative optical biopsy was capable of accurately differentiating between a healthy vs. early OA architectural fingerprint, suggesting that early OA pathology detection is indeed possible with current clinical technology [240]. Thus, such new imaging approaches, combined with modern analysis and/or predictive tools, such as AI, could be used with measurements of multiple easily measurable biochemical biomarker candidates (e.g., MMP-3 and possibly IL-17) from blood samples and combined with patient-related parameters over time and in parallel.…”
Section: Summary Outlook and Early Disease Considerationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Articular cartilage (AC) is an autonomously functioning connective tissue that absorbs and distributes the occurring mechanical joint loads. The resident cells of AC, the chondrocytes (CHs), are sparsely distributed within species-, joint type-, surface-specific [ 5 , 6 , 7 ] and diagnostically relevant [ 8 , 9 ] arrangements that are termed the superficial chondrocyte spatial organization (SCSO) and that can be used for spatial [ 10 ] and predictive modelling [ 11 ] in the context of a non-destructive quantitative optical biopsy for early disease detection. The CHs are quiescent, fully differentiated cells whose chondrogenic phenotype ensures a fine-tuned balance between anabolism and catabolism to maintain tissue homeostasis [ 12 ].…”
Section: Introductionmentioning
confidence: 99%